Manifest and Latent Function from Sar Local Wisdom of Kanum Tribe in Merauke - Anif Fatma Chawa, Trinovianto G R Hallatu, Darsono Wisadirana, Sholih Mu’adi (Opción, 2020)
Sar local wisdom is one of the local wisdoms of the Kanum tribe which still exists in order to preserve the nature and environment of the Kanum tribe itself. The principle of implementing sar itself is forbidding humans to take or process natural products from an area that is being applied sar. Aside from being a preserver of nature and the environment, sar also has a manifest function and a latent function, according to Merton’s theory. This research is a descriptive qualitative research that aims to describe the function of manifest and latent functions of local wisdom sar. The results showed that, this local wisdom has a manifest function of being an environmental and cultural preserver, increasing family ties, mutual cooperation, the value of consensus, and also the value of compliance. Whereas latent functions are balancing ecosystems, absorbing CO2 and preventing natural disasters, increasing economic value, waste of time and natural products, and the occurrence of inequality of rights between men and women.